PENGELOMPOKAN KEILMUAN DALAM ISLAM: BAYANI BURHANI, DAN IRFANI - Julita Julita; Selfiana Selfiana (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
This research discusses scientific groupings in Islam, especially from the perspective of Bahanu Burhani and Irfani. Through literature review and conceptual analysis, this study presents an in-depth understanding of these two approaches and their relationship to the development of science in the Islamic tradition. By considering aspects of methodology, epistemology and ontology, this research aims to provide comprehensive insight into the way of viewing and understanding science in the Islamic religious context. It is hoped that the findings from this research will make a significant contribution to our understanding of scientific groupings in Islam and their implications in a broader social and intellectual context